Controllable Core Size of Au@TiO2 through Al(NO3)3 Addition and Its Effects on DSSC Performance - Utama, Sangsaka Wira; Fadhilah, Nur; Haekal, Muhammad Husain; Zakaria, Rozalina; Hidayat, Rachmat; Risanti, Doty Dewi (IPTEK The Journal for Technology and Science, 2021)
It is known that plasmonic nanoparticles in dye-sensitized solar cells (DSSC) could enhance efficiency through improvement in light absorbance and electron dynamics. Herein we investigated various sizes of AuNP through spontaneous Al(NO3 )3 addition. Core-Shell Au@TiO2 was prepared with various Al(NO3 )3 concentrations of 0.25 mM, 0.5 mM, 0.75 mM and 1 mM. The Au@TiO2 volume fraction of 1% was further added to TiO2 photoanode. Based on the particle size analyzer (PSA) characteristics, the synthesized AuNP’s size was within a range of 34.62 nm – 139.5 nm. The highest efficiency of DSSC was obtained for the sample with the largest AuNP ’s diameter, i.e., 0.0313%, which is about three times higher than pristine DSSC. The increase in efficiency was in accord with Metallic Nanoparticle Boundary Element Method (MNPBEM) simulation, UV-vis spectroscopy, and Incident Photon to Current Conversion Efficiency (IPCE) analysis largest Au core diameter contributes to the strong absorbance and hence the short circuit current